Look at ROLLO! - Duncan, Reed; Frawley, Keith (New York : Penguin Workshop, an imprint of Penguin Random House LLC, 2020)
"It's Rollo's big day at the park! Time to run, play, catch the ball...and, of course, get messy along the way. Look at Rollo go!"--Back cover
"First published in hardcover in 2020 by Penguin Workshop."
Keywords: Boys -- Juvenile fiction; Bulldog -- Juvenile fiction